Предмет: Алгебра,
автор: yulechkamaksim1
СРОЧНО!!!!!СРОООЧНОО!!!РЕБЯТ,ПОМОГИТЕ!!!!
Приложения:
Ответы
Автор ответа:
1
По действиям:
1) 4 + 1 = 4 - 1 = 4 - (x+2) = 4-x-2 = 2-x =
x²-4 2-x (x-2)(x+2) x-2 (x-2)(x+2) (x-2)(x+2) (x-2)(x+2)
= -(x-2) = -1
(x-2)(x+2) x+2
2) -1 * x²+4x+4 = -1 * (x+2)² = -(x+2) = -x-2
x+2 3 x+2 3 3 3
1) 4 + 1 = 4 - 1 = 4 - (x+2) = 4-x-2 = 2-x =
x²-4 2-x (x-2)(x+2) x-2 (x-2)(x+2) (x-2)(x+2) (x-2)(x+2)
= -(x-2) = -1
(x-2)(x+2) x+2
2) -1 * x²+4x+4 = -1 * (x+2)² = -(x+2) = -x-2
x+2 3 x+2 3 3 3
Похожие вопросы
Предмет: Русский язык,
автор: AlenaAngel8779
Предмет: Английский язык,
автор: Daryana5Rodnova
Предмет: Английский язык,
автор: wer3454
Предмет: Математика,
автор: NekitPro08
Предмет: Алгебра,
автор: dushavip